Effectiveness, safety, and predictive potential in ultrasound-guided stellate ganglion blockades for the treatment of sympathetically maintained pain - Aleanakian, Ruben; Chung, Boo Young; Feldmann, Robert Enrico; Benrath, Justus (Pain practice, 2020)
Background Evaluating the effectiveness of stellate ganglion blockades (SGBs) proves challenging, since the criteria defining a successful blockade are controversial. This may be one reason for the scarcity of studies on this topic, thus forcing clinical guidelines to remain conservative in recommending SGBs. Moreover, factors to predict which patients will benefit from blockade series are not yet available. Objectives The objectives of this study were to evaluate through a clinical approach SGBs’ effectiveness performed under ultrasound guidance (us-SGB) and to identify factors to predict effectiveness. Methods We retrospectively analyzed 809 us-SGBs in 105 patients with complex regional pain syndrome (CRPS) and neuropathic pain syndromes (all potentially including sympathetically maintained pain) regarding pain reduction. Volume and type of local anesthetics, magnitude of pain, temperature of the dorsal hands, heart rate, blood pressure, and occurrence of Horner’s syndrome or complications were assessed. Results Pain reduction after a blockade series was highly significant and showed no significant correlation with change of temperature, vital signs, or Horner’s syndrome. For patients with neuropathic pain, the predictive potential for pain reduction following a blockade series lies within the range of pain reduction after the first blockade. In a literature comparison, incidences of complications (hoarseness 3.9%, dysphagia 3.4%, hematoma 0.6%) were lower than in non-ultrasound-guided techniques. Conclusions Data indicate that us-SGBs are safe and effective in reducing sympathetically maintained pain in patients with CRPS and neuropathic pain syndromes. Pain reduction after the first blockade may predict total pain reduction after a blockade series. Other clinical measures seem unsuitable to predict effectiveness.
First published: 07 April 2020
Gesehen am 18.01.2022